Viscoelasticity-induced structure anisotropy in amorphous materials. (15th January 2023) - Sheng, Ruixin; An, Zhinan; Chuang, Andew C.-P.; Xie, Xie; Liaw, Peter K.; Tong, Yang
Abstract: Viscoelasticity-induced structural change in Zr55 Cu30 Ni5 Al10 metallic glass (Zr-MG) and amorphous selenium (a-Se) is investigated using synchrotron X-ray diffraction. By analyzing the two-dimensional diffraction pattern, two types of structural anisotropy with the feature of the residual elastic strain or heterogeneous intensity of diffraction rings are revealed. The origin of the structural anisotropy is attributed to the topological rearrangement in the Zr-MG and conformation rearrangement in the a-Se. Our findings bring a structural identity to the phenomenological structureless deformation defect widely used in different amorphous materials. Graphical abstract: Image, graphical abstract